2014
DOI: 10.1073/pnas.1405135111
|View full text |Cite
|
Sign up to set email alerts
|

Conflict translates environmental and social risk into business costs

Abstract: Significance In this report we investigate company–community conflict and its role in the regulation of sustainability performance in the extractive industries. We estimate the cost of conflict to companies and identify conflict as an important means through which environmental and social risks are translated into business costs and decision-making. The paper clarifies the relationship between the environmental and social risk experienced—and interpreted—by local communities, and the business risks e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
209
0
18

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(254 citation statements)
references
References 21 publications
2
209
0
18
Order By: Relevance
“…Local and regional examples illustrate how sustainability scientists have engaged with society as change agents (4,5) and the challenges associated with such engagement (3,4,6,7). In this context, however, there has been limited attention devoted to large-scale private actors (8). Existing studies primarily focus on how major brands invest in-and benefit from-sustainability initiatives (9), or analyze how and when voluntary commitments to sustainability may influence corporate behavior (10,11).…”
mentioning
confidence: 99%
“…Local and regional examples illustrate how sustainability scientists have engaged with society as change agents (4,5) and the challenges associated with such engagement (3,4,6,7). In this context, however, there has been limited attention devoted to large-scale private actors (8). Existing studies primarily focus on how major brands invest in-and benefit from-sustainability initiatives (9), or analyze how and when voluntary commitments to sustainability may influence corporate behavior (10,11).…”
mentioning
confidence: 99%
“…As a consequence they often fail to capture positive effects from resource-led economic development (Lockie et al, 2009). Some communities focus their energy on resisting the resources sector, leading to costly delays in production, however conflict alone has limited potential to improve final outcomes for regional communities (Franks et al, 2014;Schandl and Darbas, 2008). Communities which have prepared for the establishment or expansion of extractive industries have often made effective use of dialogue to derive benefits for their community.…”
Section: Responding To Challenges At the Regional Scale: The Importanmentioning
confidence: 99%
“…A recent worldwide study of social risks and their costs for mining developments (Franks et al, 2014) has shown how disregarding the social elements in preparatory studies can develop into conflict between the community and the developers. Although these do not always lead to open clashes, the misperception of social risk and the serious undervaluing of the local community's views (usually dubbed "unfounded" or "unscientific"), has caused delays costing up to $20m per week in projects with an investment of between $3,000m and $5,000m.…”
Section: Scientific and Ethical Requirements For Preparatory Studiesmentioning
confidence: 99%
“…there is an in-depth study on ethics in SIA practice, while Vanclay et al (2013) The work of Foucault (1980Foucault ( , 2000 and more recently Flybjerg (1998Flybjerg ( , 2012Flybjerg ( , 2014 provide the necessary frame for the crucial political analysis in SIA studies. As both experience and the literature show (Franks et al, 2009(Franks et al, , 2014Esteves et al, 2012), it can be assumed that the developers' exercise of power in the local area works according to an alien logic, imported from distinct social levels. This is a paradigmatic logic (Ávila, 2006), whose ethics are imposed on others and defended as unquestionable since they are shared by the dominant positions in the network, originating outside the local context in which they are imposed.…”
Section: Scientific and Ethical Requirements For Preparatory Studiesmentioning
confidence: 99%